2013
DOI: 10.1002/ange.201209140
|View full text |Cite
|
Sign up to set email alerts
|

Generation and Structural Characterization of a Gold(III) Alkene Complex

Abstract: Gold: Ein AuIII‐Alken‐Komplex wurde hergestellt und NMR‐spektroskopisch und röntgenkristallographisch charakterisiert. Die Bindungseigenschaften wurden mit theoretischen Methoden untersucht. Die ungleichen Bindungslängen in [(cod)AuMe2]+ resultieren daraus, dass die Präferenz des 1,5‐Cyclooctadiens (cod) für nichtparallele Doppelbindungen die Rückbindung durch das Metall, die eine parallele Doppelbindung begünstigt, überwiegt.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 62 publications
1
11
0
Order By: Relevance
“…for a metalalkene complex (cod = cyclooctadiene; BARF À = [(3,5-(CF 3 ) 2 C 6 H 3 ) 4 B] À ). [22] The set of Wiberg bond indices [32] ( Table 1) (Figure 7), a result that is consistent with the detected electrophilicity toward alkoxides. The majority of the carbon atoms of 7 b gain a positive charge because gold(III) coordination provides a suitable incentive for activation of the macrocycle in the reported transformations.…”
Section: Resultssupporting
confidence: 77%
See 3 more Smart Citations
“…for a metalalkene complex (cod = cyclooctadiene; BARF À = [(3,5-(CF 3 ) 2 C 6 H 3 ) 4 B] À ). [22] The set of Wiberg bond indices [32] ( Table 1) (Figure 7), a result that is consistent with the detected electrophilicity toward alkoxides. The majority of the carbon atoms of 7 b gain a positive charge because gold(III) coordination provides a suitable incentive for activation of the macrocycle in the reported transformations.…”
Section: Resultssupporting
confidence: 77%
“…The trianionic macrocyclic core of 5 favorably matches the formal oxidation state of gold(III), whereas coordination of pal- Figure 3) [24] resembles the structure of gold(III) 5,10,15,20-tetrarylporphyrin [25] and 5,10,15,20-tetraryl N-confused porphyrin. [26] The coordination environment of the gold(III) center corresponds to the square-planar structure with the N (22), N(23), N(24), and C(21) atoms occupying equatorial positions. The macrocycle reveals the bond-length pattern expected for the aromatic free base, 5,10,15,20-tetraaryl-21-carbaporphyrin.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This suggestion is reinforced by recent theoretical results from Tilset and co‐workers, who studied the degree of backbonding in the gold(III) alkene complex [(cod)AuMe 2 ][BAr F ] and compared it to that of the neutral Pt II complex. They found that the metal d xz and d yz orbitals backdonated into the π* orbital of the alkene, but the contribution was weaker, though still significant, in the gold(III) complex 16…”
Section: Resultsmentioning
confidence: 99%